Modos de formar professores de EJA- 1990- 2006 - Bernardes, Fernanda Afonso (2016)
ABSTRACT: This study aimed to analyse the ways of learning and teaching in EJA in the 1990 period to 2006 in Uberlândia city located in Minas Gerais. The time frame initially corresponds to the international year for literacy, and end corresponds to implementation of the new pedagogy course guidelines. The specific objectives were identify and analyze the conceptions of training literacy teachers during the 1990 period to 2006, analyze the correspondence between training and practice of literacy teachers of EJA, unveiling the narratives of literacy teachers and coordinators, mapping out his recollections of the initial training process to work in EJA. The study was conducted using as a methodological reference the thematic oral history, crossing with documental and the literature. In this sense, document consultation were held in the Public Archives of Uberlândia. Uberlândia City Hall and Municipal Center for Education Studies and Projects (CEMEPE). Federal University of Uberlândia, as well as conducted a literature search, especially about the eja history, teacher training and pedagogy course. Among the documentary sources appealed too, the newspapers. To understand the context of the problem investigated, resumed the debate on teachers training and their knowledge, the institution of Youth and Adult Education as a right, and we sought to demarcate the historical EJA characteristics in the country, in Minas Gerais and finally in Uberlândia. It found that issues related to teachers training to work in EJA was to be desired, since the three institutions have not favored this area in the curriculum, the right to education proclaimed since the republic was only in the speeches. It was also found that changes in municipal administration, because of the alternation of parties in government, in the period studied, determined changes in the PMEA, it has transformed into a public policy although marked by a series of problems. Keywords: Initial Training, Youth and Adult Education, PMEA